Religions and Legal Regimes Function in the Protection of Children - Adebayo, Akintunde Abidemi (Faculty of Law, Universitas Negeri Semarang, 2020)
Religion provides the basis for the protection of human rights, namely, the right to life, the dignity of the human person, and right to property, among others. Without prejudice or disrespect to other religions, this paper focuses on Christianity religion and its provisions that protect the rights of children considering their vulnerability. This research emphasized that the Holy Bible contains measures to safeguard, protect and ensure the good as well as the proper upbringing of children. Similarly, the United Nations Convention on the Rights of the Child 1989, OAU Charter on the Rights and Welfare of the Child 1990 and the Nigerian Child Rights Act, 2003 provide for the protection of rights of children. The essence of these provisions is to ensure the smooth running of society and the betterment of humanity. This paper, therefore, examines the salient provisions of the Holy Bible and legal regimes to safeguard and protect the rights and interests of children. It concludes by highlighting the significant role of laws in the protection of the rights of children. It also shows that religion plays a pivotal role in protecting the interests of children by instilling in members of the society, the needed respect for humanity and morality, which is mostly lacking in the modern era. It recommends, among other things that, government at all levels as well as religious leaders, should give priority attention to the protection of children.